South Africa's democracy at the crossroads - Silander, Daniel; Silander, Charlotte; Elst, Herman van der; Heydenrych, Pieter (Emerald Publishing Limited, 2022)
Since the first elections of 1994, the South African constitution officially guarantees and promotes a wide range of political and civil rights and institutionalizes the separation of powers with an independent judiciary. This has made South Africa a political symbol of change, hope and democracy in Africa and around the world. However, since the introduction of free and fair electoral processes and with ANC dominating the presidency and the parliamentary seats, the political scene has been scattered by democratic challenges. South Africa remains a flawed democracy, combining free elections and respect for basic civil liberties with problems of governance, an underdeveloped political culture, and low levels of public participation. Today, South Africa stands at a crossroads. While the constitutional democracy has survived, South African democracy seems to have weakened by state capture, internal ANC implosion, corruption, societal polarization, social exclusion, xenophobia, and threats of state economic bankruptcy. South Africa faces growing discontent symbolized in intensified societal and political debates, protests and demonstrations providing for the question if this is a sign of dissatisfied citizens demanding deeper democracy or activities questioning the established constitutional democracy from an anti-democratic, populist, and radical point of view. South Africas Democracy at the Crossroads explores the question; what are the challenges to future democratization in South Africa?
Includes index.
Keywords: Democracy -- South Africa.; Political Science -- Political Ideologies / Democracy.; Political structures: democracy.; elektronické knihy; electronic books